Students’ Mathematical Representation in Geometry Problem-Solving: A Case Study on Fifth Class at SDN Brangkal 1 - Ernamasari, Navalia Dewi; Riyadi, Riyadi; Roslan, Roslinawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Elementary school students tend to rely on memorizing formulas to solve mathematical problems. They do not yet understand the visual meaning of mathematical concepts, which affects their ability to represent ideas well. This study seeks to investigate students’ abilities to use mathematical representation when solving problems involving 2D geometric shapes. The study employed a qualitative research approach using a case study design. Data were collected through interviews with the classroom teacher and ten students at SDN Brangkal 1 and analyzed using thematic coding techniques. The findings revealed that most students continue to rely on memorizing formulas without grasping the visual meaning of 2D shapes. They seldom use diagrams, rarely verify answers, and struggle to articulate the reasoning behind their problem-solving steps. In addition, the students demonstrated limited verbal representation skills, often providing brief, unexplained responses and showing little habit of expressing their thought processes. These results suggest that students' competence in mathematical representation within the domain of geometry remains low. The findings underscore the need for instructional strategies that integrate visual, symbolic, and verbal representations, and cultivate habits of reflection and communication in primary school geometry education.